Variation of Sea Turtle Hatch Morphology in Bantul Coast - Nurul Isnaini; Sulistiyawati Sulistiyawati (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2019)
This study aimed to determine the variation of sea turtle morphology on the Bantul Coast. Morphometric measurements of sea turtle species (Lepidochelysolivaceae) were done and its morphology was observed. The results of the research were six morphological characters which showed significant differences between hatchlings on Pelangi and Goa Cemara Coast. The morphology between sea turtle hatchlings and the number of carapace 6 pairs, 7 pairs and 8 pairs obtained four significant differences.